2023
DOI: 10.1039/d2py01512a
|View full text |Cite|
|
Sign up to set email alerts
|

One pot synthesis of thiol-functional nanoparticles

Abstract: Polysorbate 80 (PS80) was reacted with 3-mercaptopropyl trimethoxysilane (SiSH) via a photoinitiated thiol-ene reaction. The conjugate was then mixed with SiSH and water to form uniform thiol-functional nanoparticles (TFNs) approximately...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…[24][25][26][27][28] Our initial work on RAFT PISA printing utilized a difunctional poly(ethylene glycol) (PEG) macro-CTA, chain extended with diacetone acrylamide (DAAm) in water, and 3D printed via DLP using lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) as a photo-initiator and phenol red as a photoabsorber. 29 In this study, we observed the dissolution behavior of DAAm PISA frogs in N,N-dimethylformamide (DMF), noting that those without N′N-methylene bisacrylamide (MBAc) crosslinker dissolved completely, indicating the presence of physical crosslinks. Building on this foundation, our second PISA printing study aimed to develop formulations capable of dissolving in physiological fluids with controlled kinetics.…”
Section: Introductionmentioning
confidence: 95%
“…[24][25][26][27][28] Our initial work on RAFT PISA printing utilized a difunctional poly(ethylene glycol) (PEG) macro-CTA, chain extended with diacetone acrylamide (DAAm) in water, and 3D printed via DLP using lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) as a photo-initiator and phenol red as a photoabsorber. 29 In this study, we observed the dissolution behavior of DAAm PISA frogs in N,N-dimethylformamide (DMF), noting that those without N′N-methylene bisacrylamide (MBAc) crosslinker dissolved completely, indicating the presence of physical crosslinks. Building on this foundation, our second PISA printing study aimed to develop formulations capable of dissolving in physiological fluids with controlled kinetics.…”
Section: Introductionmentioning
confidence: 95%